Dexmedetomidine versus Magnesium Sulfate as Adjunct during Anesthesia for Laparoscopic Colectomy - Pierre Zarif; Ahmed Abdelaal Ahmed Mahmoud; Mohamed Mohamed Abdelhaq; Hany M. S. Mikhail; Ahmed Farag (Anesthesiology Research and Practice)
Objectives. To compare dexmedetomidine versus magnesium during laparoscopic colectomy. Patients and Methods. 51 patients were randomly allocated into 3 groups: group C (control) received saline infusion, group D dexmedetomidine 1 g/kg and then 0.4 g/kg/hr, and group M MgSO4 2 g and then 15 g/kg/min. Intraoperative hemodynamics were measured before and 1 min after intubation (T1 and T2), before and 5 min after peritoneal insufflation (T3 and T4), before and 5 min after 30° Trendelenburg position (T5 and T6), 5 min after resuming flat position (T7), 5 min after peritoneal deflations (T8), after extubation (T9), and at time of admission to PACU (T10). Recovery time and degree of sedation were assessed. Results. HR and MAP were significantly higher in T2, T4, and T6 compared to T1, T3, and T5, respectively, in all groups with lower measurements in groups D and M compared to group C. Mean of collective measurements was significantly higher in group C. Recovery time and sedation score were significantly higher in groups D and M. Time to Aldrete score of ≥9 was significantly longer in groups D and M. Conclusion. Both drugs ameliorate the pressor responses during LC with a nonsignificant difference. This study is registered with PACTR201602001481308.